Isolation of Cellulolytic Bacteria from the Soil Surrounding a Final Landfill Site - Latusi Anggriani; Fily Larasari; Dewinta Nur Alvionita (DIVERSITAS HAYATI, 2023)
Cellulolytic bacteria are capable of producing cellulase enzymes, enabling them to break down cellulose into simpler compounds using cellulose as a growth substrate. These bacteria are commonly found in various environments containing cellulose, such as landfill sites where abundant organic materials are present. This research employed the cup-plate isolation method with the aim of obtaining cellulolytic bacterial isolates from the soil surrounding a final landfill site. Successful isolation of cellulolytic bacteria was achieved from soil samples taken in proximity to the disposal site and cultured using selective CMC media. Two purified isolates were obtained, and their cellulase enzyme activities were examined. Isolate LA2 exhibited higher cellulase enzyme activity than isolate LA1, forming a clear zone index of 0.7778. Further quantitative analysis of isolate LA2 revealed its highest enzyme activity at the fifth minute, measuring 0.098 u/ml with a specific activity of 0.29 u/mg protein. Based on physiological characteristics, Gram staining, and spore staining, isolate bacteria LA2 were identified as Pseudomonas sp.